2004
DOI: 10.1177/0888439004267674
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Neurophysiological Assessment of Residual Motor Control in Post-Spinal Cord Injury Paralysis

Abstract: Multimuscle surface electromyography patterns recorded during a rigidly administered protocol of motor tasks can be used to differentiate between clinically paralyzed spinal-cord-injured individuals using subclinical motor output to identify the translesional neural connections that remain available for intervention testing and treatment planning after spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
83
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 26 publications
8
83
0
Order By: Relevance
“…This was discussed in another publication of our group. 2 Previous work using sEMG has shown that as motor control deteriorates during a fatiguing voluntary motor task in healthy subjects, muscles not involved in the task begin to coactivate, and coactivation continues to increase during the period of the exercise. 28 Also, using sEMG as an objective measure of coactivation, Thomas et al 29 noted that muscles 'weakened by SCI' require near-maximal effort and activation that is accompanied by synergistic activation of other antagonistic muscles that further exacerbates the weakness of the movement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was discussed in another publication of our group. 2 Previous work using sEMG has shown that as motor control deteriorates during a fatiguing voluntary motor task in healthy subjects, muscles not involved in the task begin to coactivate, and coactivation continues to increase during the period of the exercise. 28 Also, using sEMG as an objective measure of coactivation, Thomas et al 29 noted that muscles 'weakened by SCI' require near-maximal effort and activation that is accompanied by synergistic activation of other antagonistic muscles that further exacerbates the weakness of the movement.…”
Section: Discussionmentioning
confidence: 99%
“…However, lesions clinically judged as complete often retain residual supraspinal connectivity not clinically recognizable. 1,2 For motor incomplete spinal cord injured (iSCI) subjects, partially disrupted voluntary control of lower-limb muscles determines many aspects of their recovery following the acute phase post injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in individuals with severe SCIs, some spared trans-lesional systems, descending long-tract fibers or propriospinal fibers, are nearly always present. 15,16 It has been shown that the remaining altered spinal cord circuits below the injury can be activated and modified by transcutaneous spinal cord stimulation. 17 We suppose that in patients in whom the vestibulospinal pathways remained preserved, the altered spinal cord circuits below the injury could be conditioned by activation of the vestibulospinal pathways.…”
Section: Introductionmentioning
confidence: 99%
“…14,22 While the Ashworth and modified Ashworth scales 14,15,23 are commonly used to assess the severity of spasticity, there is some question about their validity in the lower limbs of persons with SCI. 24 As spasticity outcomes vary between clinical patient groups and depend on a variety of factors within each individual, a battery of assessment tools is recommended, incorporating clinical, electrophysiologic, neurophysiological, 25 and/or biomechanical techniques. 14,26,27 It is important to note that there are generally poor correlations among clinical scales and, further, reductions in spasticity are not necessarily correlated with improvement in function.…”
Section: Introductionmentioning
confidence: 99%